1997
DOI: 10.1021/ja9709278
|View full text |Cite
|
Sign up to set email alerts
|

1,1,3,3-Tetraoxo-1,2,3-triazapropene Anion, a New Oxy Anion of Nitrogen:  The Dinitramide Anion and Its Salts

Abstract: We report the synthesis of a completely new, stable class of inorganic salts named the dinitramide salts. These salts are based on a newly discovered nitrogen oxide anion known as the dinitramide anion. The dinitramide anion is a uniquely stable, high oxygen density grouping that can be prepared in many salt combinations including the ammonium or hydrazinium salts. The dinitramide anion has both fundamental scientific interest and practical applications. We describe here the synthesis of dinitramide salts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 22 publications
2
87
0
Order By: Relevance
“…b) KDN is a member of the dinitramide anion ]. The presence of dinitramide anions imparts a high heat of formation, density, and oxygen balance [14]. There are numerous other synthesized DA-based energetic compounds with many possible applications [15] When this complex cools down to room temperature, it slowly converts to the tetramine complex which stabilizes AN [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…b) KDN is a member of the dinitramide anion ]. The presence of dinitramide anions imparts a high heat of formation, density, and oxygen balance [14]. There are numerous other synthesized DA-based energetic compounds with many possible applications [15] When this complex cools down to room temperature, it slowly converts to the tetramine complex which stabilizes AN [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Covalent dinitramides are less stable than the ionic dinitramides, which is in accordance with stability differences between the corresponding covalent and ionic nitrates and nitrites respectively. [23] The reason for instability of a covalent dinitramide moiety likely is the result of a sterical hindering of the two nitro-groups, which is significantly different to an ionic dinitramide, and the comparatively high electronegativity of the N,Ndinitro-group. Furthermore the absence of an additional electron, which accounts in the dinitramide-anion for resonance stabilization and thereby resulting in a higher N-N bond order, decreases the stability.…”
Section: Resultsmentioning
confidence: 99%
“…[24] Therefore the few up to now reported alkyldinitramines decompose at temperatures below 70 °C and are extremely shock sensitive. [23] In summary the first covalent organotellurium(IV) bis(dinitramides) were synthesized by reaction of the organotellurium(IV) dihalides with silver dinitramide or with trimethylsilyl dinitramide as a new dinitramide transfer reagent. The silyl derivative could also be characterized by multinuclear NMR spectroscopy and its limited stability was noted.…”
Section: Resultsmentioning
confidence: 99%
“…After 5 min of irradiation, the NO 2 − /NO 3 − ratio was relatively high, reaching 4.4, which is in line with the ratio of 4 obtained by Mill et al 13 during photolysis of ammonium dinitramide in water (pH 7). The NO 2 − /NO 3 − ratio decreased to 0.37 after 7 days, indicating that NO 2 − might have been photo-oxidized to NO 3 − . 19 In an earlier study involving photolysis of the nitramine RDX, (NO 2 −NCH 2 ) 3 ,we found that NO 2 − formed from the photocleavage of N−NO 2 can be photooxidized to NO 3 − .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The latter being unstable should undergo spontaneous decomposition to give NO 2 − ,N 2 O, and water. 13 It is known that photolysis of NO 2 − can lead to NO 3 − . 19,20 When another FOX-12 aqueous solution was incubated with the bacterium Variovorax strain VC1 without light, guanylurea degraded to guanidine, ammonia, and presumably CO 2 but, this time, leaving dinitramide intact (route c in Figure 6).…”
Section: Ohmentioning
confidence: 99%